Articulation within (and across) transnational workplaces and the role of European Works Councils. (September 2017) - Pulignano, Valeria
Trade unions often make concessions on wages and working conditions when confronted with threats of job losses by management within multinational companies. However, articulating European Works Councils (EWCs) activities with industrial relations institutions and actors at different levels can help maintain job stability while guaranteeing good working conditions. This article draws on a comparative analysis of eight multinational subsidiaries in Britain, Belgium, Germany and Italy to illustrate how this can be achieved. In particular, through strengthening EWCs and negotiating European Framework Agreements, unions can constrain management benchmarking strategies and spread across countries the positive gains of local negotiations where unions are strong to other subsidiaries where they struggle to negotiate on employment protection.